1990
DOI: 10.1093/bja/64.5.542
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on the Spread of Spinal Analgesia After Injection of Plain 0.5% Bupivacaine at the L3–4 or L4–5 Interspace

Abstract: Spinal anaesthesia was compared in 40 obese patients (increased body mass index (BMI] and 40 patients with normal BMI when 3 ml of plain 0.5% bupivacaine was injected at either the L3-4 or L4-5 interspace. More extensive cephalad spread of sensory block was achieved in patients with increased BMI compared with patients with normal BMI after injection at both L3-4 and L4-5 (P less than 0.05). The use of the L3-4 interspace instead of L4-5 resulted in a higher mean spread of block in patients with both increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 0 publications
4
59
1
1
Order By: Relevance
“…Similar to the results of the current study, several studies in non-pregnant adults found increased BMI was associated with a higher cephalad sensory level when local anesthetic solutions were administered at doses necessary for surgical anesthesia. [7][8][9][10][11] There was a large variability in cephalad sensory levels following intrathecal injection of a hypobaric solution in the current study, similar to studies of isobaric and hyperbaric solutions. There have been several small series of case reports in which parturients had sensory blockade of cranial nerves after initiation of CSE analgesia.…”
Section: Objectif : Déterminer Si L'étendue Du Blocage Sensitif Suivsupporting
confidence: 64%
“…Similar to the results of the current study, several studies in non-pregnant adults found increased BMI was associated with a higher cephalad sensory level when local anesthetic solutions were administered at doses necessary for surgical anesthesia. [7][8][9][10][11] There was a large variability in cephalad sensory levels following intrathecal injection of a hypobaric solution in the current study, similar to studies of isobaric and hyperbaric solutions. There have been several small series of case reports in which parturients had sensory blockade of cranial nerves after initiation of CSE analgesia.…”
Section: Objectif : Déterminer Si L'étendue Du Blocage Sensitif Suivsupporting
confidence: 64%
“…These outcomes indicated that both of the levobupivacaine doses that were used in a geriatric patient population were safe. When the literature was evaluated, height and body weight were among the other demographic features that affect spinal anesthesia level [6,18]. In our study, the groups were similar in all of these factors.…”
Section: Discussionsupporting
confidence: 55%
“…Levobupivacaine is an S(-) enantiomer of bupivacaine and a long-acting local anesthetic with an amide structure [5,6]. Levobupivacaine is available in isobaric form in 0.25%, 0.5% and 0.75% concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Dose requirements for operative SABs are 75-80% of normals $7-59 but are somewhat more variable than normal. 59 In fit MO patients SAB to T5 produces little change from baseline in respiratory volumes 6~ and blood gases. 6~ However, if the block extends above T5 there is a risk of respiratory compromise, especially in those patients with preexisting respiratory disease.…”
Section: Regional Anaesthesiamentioning
confidence: 94%